An Investigation into Morphological and Phonological Features of Graphemes in Native Speakers and Vietnamese Learners of English - Lê Nguyễn Ty Na (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This thesis aims to study the morphological and phonological features of graphemes experienced by native English speakers and Vietnamese learners of English. Based on some theoretical preliminaries that covered a review of such aspects of graphemes, phoneme, morpheme, relevant theories as Generative theory and Optimality theory, and the snapshot of graphemes in English and Vietnamese; the morphological and phonological features of graphemes are demonstrated. The morphological features of graphemes experienced by native English learners and Vietnamese learners of English, and their roles are determined by the morphological analysis of types of errors made by participants in terms of the inflectional plural morphemes. In addition, the phonological features of graphemes experienced by native and Vietnamese participants, and their effects on the encoding process are examined through the phonological analysis of types of errors made by participants in terms of silent graphemes, vowel grapheme, consonant doublets and consonant clusters with different positions of phonemes in words and syllables. The data are collected from 200 samples of spelling performances made by native English speakers and Vietnamese learners of English at their beginner level. As a result, it is proved that the morphological features of graphemes are considered as a signpost for the encoding process. Moreover, phonological features of graphemes express fully the phonological features of phonemes that they represent. In addition, phonological features of graphemes affect spelling performance with different positions of phonemes in words and syllables.